Visual inspection and microhardness based studies of friction welding of tube to tube plate using an external tool. (2020) - Deepesh, V.; Purushothaman, Amal V.; Muthukumaran, S.; Sastikumar, D.
Abstract: Conventional Friction welding is a well-established solid state welding process. However, this method has a limitation that it is not suitable for tube to tube plate welding. An innovative variant of this process, named Friction welding of tube to tube plate using an external tool (FWTPET) is gaining popularity in industrial applications as a potential alternative to its fusion welding counter parts. This process can be used to join not only similar but also dissimilar metals. The major parameters of this process include the speed of rotation of the tool, plunge depth and plunge duration. In this work, the effect of plunge duration and tool rotational speed on the quality of FWTPET process is investigated using visual examination and microhardness analysis of tube to tube plate joints between two grades of Aluminium alloys welded under various conditions. The results of the visual inspection are used to examine the parameters for optimal flash deposition without causing excessive internal material loss. The effect of plunge duration and tool rotation speed, on the microhardness of the weld, is also studied in this work and the results show that at higher plunge durations and tool rotational speeds, the micro hardness tends to drop. Microstructural analysis shows that the grain coarsening happens due to dynamic recrystallization, similar to that in Friction Stir Welding.